2001
DOI: 10.1094/mpmi.2001.14.11.1327
|View full text |Cite
|
Sign up to set email alerts
|

A Protein from the Mold Aspergillus giganteus Is a Potent Inhibitor of Fungal Plant Pathogens

Abstract: A purified preparation of antifungal protein (AFP) from Aspergillus giganteus exhibited potent antifungal activity against the phytopathogenic fungi Magnaporthe grisea and Fusarium moniliforme, as well as the oomycete pathogen Phytophthora infestans. Under conditions of total inhibition of fungal growth, no toxicity of AFP toward rice protoplasts was observed. Additionally, application of AFP on rice plants completely inhibited M. grisea growth. These results are discussed in relation to the potential of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 12 publications
0
31
0
Order By: Relevance
“…Since AFP is an extracellular protein, the potential involvement of its two binding abilities, to membranes and DNA, in its antifungal action should be considered. In regard to this, it has been reported that AFP completely inhibits the growth of phytopathogenic fungi in rice with no toxicity toward plant protoplasts (38) and that heterologous expression of the afp gene enhanced fungal resistance in transgenic wheat (39), which opens the potential use of the afp gene to enhance crop protection against fungal pathogens in transgenic plants. Finally, the activity of AFP on promoting DNA condensation and interacting with lipid membranes may also be useful in designing non-viral gene delivery systems.…”
Section: Resultsmentioning
confidence: 99%
“…Since AFP is an extracellular protein, the potential involvement of its two binding abilities, to membranes and DNA, in its antifungal action should be considered. In regard to this, it has been reported that AFP completely inhibits the growth of phytopathogenic fungi in rice with no toxicity toward plant protoplasts (38) and that heterologous expression of the afp gene enhanced fungal resistance in transgenic wheat (39), which opens the potential use of the afp gene to enhance crop protection against fungal pathogens in transgenic plants. Finally, the activity of AFP on promoting DNA condensation and interacting with lipid membranes may also be useful in designing non-viral gene delivery systems.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition zones which mediated by AFP as different concentrations demonstrated a positive relation between the concentration and the activity (Figure 5). This may be due to the influence on AFP hyphal extension by localisation on the outer membrane within defined areas cause short, thick and highly septated hyphae with constricted apical regions extruding from condensed mycelia [12] [29]. However, AFP shares several structural features with membrane acting proteins, such as an amphiphitic structure, a basic PI and the occurrence of eight cysteine residues, all involved in intermolecular disulfide bridges.…”
Section: Discussionmentioning
confidence: 99%
“…One thousand spore or conidia were added to 200 µl of culture medium containing AFP at different concentrations ranged from 0 -50 µg•ml −1 in microtiter plate (Greiner, Frickenhausen). After 72 h of incubation with continuous agitation at 120 rpm, the mycelium from each concentration was washed with phosphate buffer (pH, 7.0) then fixed with Poly-L-Lysine (PLL) on glass slid and covered with slid cover [29]. The morphological attributes were microscopically diagnosed.…”
Section: Determination Of the Morphological Changesmentioning
confidence: 99%
“…The in vitro antifungal activity of both P. pastoris-produced recombinant AFPs, as well as the A. giganteus-produced natural AFP, was determined using a microtiter plate assay as previously described [13,15,28]. Briefly, 90 μl of a fungal spore suspension at 10 5 spores/ml in PDB (potato dextrose broth; DIFCO, Detroit, MI, USA), containing 0.003% (wt/vol) chloramphenicol, was allowed to pre-germinate for 6 h at 28°C.…”
Section: In Vitro Antifungal Activity Of the Purified Proteinsmentioning
confidence: 99%
“…One of these promising polypeptides is the antifungal protein (AFP) secreted by the mould Aspergillus giganteus. AFP is a basic, low molecular weight (51 residues long) protein showing in vitro antifungal properties against important plant pathogens, including Magnaporthe oryzae, Fusarium verticilloides, Phytophthora infestans, and Botrytis cinerea [11][12][13][14][15]. These fungi are responsible for important diseases in a large number of plants with agricultural and economical importance, such as rice, wheat, potato, or tomato.…”
Section: Introductionmentioning
confidence: 99%